Da'wah Nahdlatul Ulama In Increasing Tolerance Between Religious Communities - Siti Wuryan; Mustofa, Muhamad Bisri; M. Nasor; Fauziah Hassan (Moderatio: Jurnal Moderasi Beragama, 2025)
Inter-religious tolerance is essential in maintaining social harmony and harmony in society. In Indonesia, Nahdlatul Ulama (NU) is an Islamic organization that has a major role in advocating the values of tolerance and diversity. In the context of Wana Village, Melinting Subdistrict, East Lampung Regency, the role of NU in strengthening interfaith tolerance is the main focus of this research. This research uses a qualitative approach with data collection techniques that include direct observation in the field, face-to-face interviews with informants, and documentation. Primary data was obtained directly from informants regarding NU's da'wah methods in improving interfaith tolerance in Wana Village, while secondary data included books, journals, scientific papers, and other online sources. The results showed that in Wana Village, the role of the Nahdlatul Ulama community in improving interfaith harmony is very important. As the religious majority and the largest group of religious adherents in the village, the NU community has a great responsibility in maintaining existing pluralism. Not only that, the role of the NU community also includes various efforts that must be carried out to maintain inter-religious harmony. In a life of tolerance, an attitude of openness, acceptance, and respect for differences is very important to maintain.